Clean water recycling through adsorption via heterogeneous nanocomposites: Silver-based metal-organic framework embellished with graphene oxide and MXene. (June 2023) - Dadashi Firouzjaei, Mostafa; Zolghadr, Ehsan; Arabi Shamsabadi, Ahmad; Sadrzadeh, Mohtada; Rahimpour, Ahmad; Akbari Afkhami, Farhad; Wujcik, Evan K.; Elliott, Mark
Abstract: Cationic methylene blue (MB) and anionic orange G (OG) dyes were adsorbed using the first-ever synthesized nanocomposite of MXene-AgMOF. At 200 mg/L and 0.01 g, GO-AgMOF, MXene-AgMOF, and AgMOF were able to adsorb 99.9%, 99.0%, and 98.0% of cationic MB dye, respectively, from water. The nanocomposites were characterized both before and after adsorption using different characterization techniques. These nanocomposites show promise as cationic contaminant adsorbents, with an adsorption capacity of 399.9 mg/g for GO-AgMOF. Also, the enhanced adsorption capacity of AgMOF for anionic and cationic dyes suggests its potential use in environmental remediation when combined with MXene. Graphical abstract: Image 1